2015
DOI: 10.1177/0959683615585835
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking the spread of agriculture to the Tibetan Plateau

Abstract: New data from the Tibetan Plateau allow us to understand how populations dealt with the challenges of moving crops into altitudinally constrained environments. Despite the interest in explaining the timing and the mechanisms via which agricultural products spread to the roof of the world, current models for the spread of agriculture to this region have been simplistic and the presence of crop domesticates is often straightforwardly interpreted as indicating the existence of an agricultural system at the site. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(24 citation statements)
references
References 75 publications
0
23
0
1
Order By: Relevance
“…In our study area, human activity dates back to at least 5000 14 C years before present (Liu et al ., ), suggesting that there were people living in the areas we sampled prior to the time the oldest terraces we sampled formed. However, the degree to which individuals in these settlements were engaged in agriculture is currently debated (d'Alpoim Guedes, , ). Thus it is possible that the 10 Be i concentrations in terrace sediments were affected by early human activities in China.…”
Section: Discussionmentioning
confidence: 99%
“…In our study area, human activity dates back to at least 5000 14 C years before present (Liu et al ., ), suggesting that there were people living in the areas we sampled prior to the time the oldest terraces we sampled formed. However, the degree to which individuals in these settlements were engaged in agriculture is currently debated (d'Alpoim Guedes, , ). Thus it is possible that the 10 Be i concentrations in terrace sediments were affected by early human activities in China.…”
Section: Discussionmentioning
confidence: 99%
“…However, during the 4th millennium BP, worldwide temperatures became cooler (Marcott et al, 2013), and may have led to difficulties in millet cultivation. Evidence shows major shifts in proso millet farming on the Tibetan Plateau until its cultivation was abandoned in Eastern Tibet (Guedes et al, 2014, 2015a,b; Chen et al, 2015; Guedes, 2015). Later, proso millet was largely replaced by wheat and barley on the Tibetan Plateau; however, it continued to be a popular crop in low-lying plains of northern China well after its introduction (Boivin et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Recent data from the southeastern and northeastern Tibetan Plateau (SETP and NETP, respectively; fig. 1) have shown that, following two millennia of broomcorn and foxtail millet cultivation in the margins of the Tibetan Plateau, these crops were largely abandoned in favor of two newly introduced domesticates: wheat and barley (Chen et al 2015;d'Alpoim Guedes 2013, 2015d'Alpoim Guedes, Bocinsky, and Butler 2015;d'Alpoim Guedes and Butler 2014;Dong et al 2015). However, to date, explanatory frameworks have only rarely used models to predict how these crops were impacted by changes in climate over the course of the Holocene (d'Alpoim Guedes 2013; d'Alpoim Guedes, Bocinsky, and Butler 2015; d'Alpoim Guedes and Butler 2014;.…”
mentioning
confidence: 99%